(2x+3)-(y+3)=

Simple and best practice solution for (2x+3)-(y+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+3)-(y+3)= equation:


Simplifying
(2x + 3) + -1(y + 3) = 0

Reorder the terms:
(3 + 2x) + -1(y + 3) = 0

Remove parenthesis around (3 + 2x)
3 + 2x + -1(y + 3) = 0

Reorder the terms:
3 + 2x + -1(3 + y) = 0
3 + 2x + (3 * -1 + y * -1) = 0
3 + 2x + (-3 + -1y) = 0

Reorder the terms:
3 + -3 + 2x + -1y = 0

Combine like terms: 3 + -3 = 0
0 + 2x + -1y = 0
2x + -1y = 0

Solving
2x + -1y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'y' to each side of the equation.
2x + -1y + y = 0 + y

Combine like terms: -1y + y = 0
2x + 0 = 0 + y
2x = 0 + y
Remove the zero:
2x = y

Divide each side by '2'.
x = 0.5y

Simplifying
x = 0.5y

See similar equations:

| 4x-(0.56x-1.33)= | | 5=-3x-29 | | 31=a-57 | | 11x-6-6x=6x-4 | | 4-7sinex=0 | | t-8=26 | | z+16=17 | | 4-7sinx=0 | | 2t-1/1-4t^2 | | 6x+2=6(3)+2 | | b+44=52 | | 4.5=1.2timesw | | 9x+2=-3+4x | | 15w^2+31w-28=0 | | 0.05x-0.03y=9 | | 6b=52 | | 7m-25=24 | | 11n+5=137 | | 51-6x=21 | | p/2=6 | | -2x-5y=20 | | 14x+6=2(5x+3) | | 2.5x+48.9=15.0-8.8x | | 2(5x-2)-x=40 | | 17x-12y=-36 | | 3xy/9x | | (m-1)x^2-2(m+1)x+m+4=0 | | 2x+1y=-10 | | -6=5-11n | | a^2+9a-9fora=-9 | | -5X+2Y=-40 | | x+2x+6x+2=29 |

Equations solver categories